TVP-VAR Analysis of NFT, DeFi, Assets, and Clean Energy in Investment Portfolio - Malhotra, Nidhi (Indian Journal of Finance, 2025)
Objective : This study explored the intricate connections between conventional investments, digital assets, and renewable energy in a rapidly changing financial environment that has been influenced by the COVID-19 pandemic, geopolitical tensions, and changing market trends. Analyzing these assets’ interactions and evaluating their contribution to risk transmission and diversification were the goals. Design/Methodology/Approach : This study analyzed daily return data encompassing a range of market situations from January 2, 2020, to January 2, 2023, using a time-varying parameter vector autoregression (TVP-VAR) model. The model captured dynamic interdependencies and spillover effects between asset types. Findings : The results showed that financial markets were closely related to one another and that interactions were more intense during significant shocks. While digital asset markets, such as cryptocurrencies and NFTs, acted as shock receivers to varied degrees, crude oil emerged as the primary shock transmitter. The greatest susceptibility to market disruptions was shown by Bitcoin and Chainlink, whereas NFTs showed less vulnerability, confirming their usefulness as tools for portfolio diversification. The growing importance of clean energy assets in investment strategies was reflected in their increasing alignment with digital financial markets. Practical Implications : By emphasizing the best asset allocation techniques during financial crises, the study offered insightful information to investors, asset managers, and legislators. NFTs and clean energy assets may improve portfolio resilience, according to the research, and regulatory frameworks ought to take into consideration the volatility spillovers of digital financial instruments. Originality/Value : By combining clean energy equities, digital assets, and conventional investments into a single dynamic connectivity paradigm, this study added to the body of prior research. By highlighting the strategic significance of digital assets and sustainable investments in contemporary portfolio management, the study advanced knowledge of financial contagion.